Design strategy for controlled natural aging in Al–Mg–Si alloys. (1st October 2016) - Werinos, M.; Antrekowitsch, H.; Ebner, T.; Prillhofer, R.; Curtin, W.A.; Uggowitzer, P.J.; Pogatscher, S.
Abstract: This study presents a design strategy for Al–Mg–Si alloys to control natural aging. Recently, trace addition of Sn was shown to suppress natural aging for up to two weeks, which was explained by the strong trapping of vacancies to Sn atoms. Here we explore the effect of solution treatment temperature, the combination of trace elements such as Sn and In, and the composition of main hardening elements Mg, Si and Cu on natural aging. The results are discussed based on the dissolvable amount of trace elements and their effect on diffusion retardation, and solute clustering mechanisms in Al–Mg–Si alloys. Thermodynamic calculations using the CALPHAD approach show that maximum retardation of natural aging is achievable at the highest trace element solubility, which exists at significantly different solution treatment temperatures for Sn or In. The effects of Mg, Si and Cu content on natural aging kinetics are interpreted via their influence on the Sn solubility and clustering mechanisms. It is proposed that Sn additions reduce the concentration of excess vacancies, which is most important for early Si clustering, and that the effect of Cu is comparable to the effect of Sn, but less pronounced. Based on the investigated parameter space, a design concept is proposed and an Al–Mg–Si alloy showing suppression of natural aging for >6 months and significant artificial aging potential is demonstrated. Graphical abstract: